2021
DOI: 10.1111/aor.14109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UNOS policy change and exception status request on outcomes in patients bridged to heart transplant with an intra‐aortic balloon pump

Abstract: In patients bridged with IABP, UNOS policy change is associated with better waitlist outcomes but no difference in post-HTx survival. Exception status use increased after policy change, but not associated with waitlist outcomes or post-transplant survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…As shown by Gonzalez et al, 3 there was both a substantial waitlist and post-transplant survival benefit in VA-ECMO bridged patients during the POST era. Similarly, we previously observed 12 significant waitlist benefits for POST era IABP-supported (status 2) patients bridged to heart transplantation without any difference in post-transplant survival. Additionally, our analysis identified a nearly 3-fold increase in the number of patients undergoing heart transplantation from mechanical ventilation.…”
Section: Limitationssupporting
confidence: 71%
See 2 more Smart Citations
“…As shown by Gonzalez et al, 3 there was both a substantial waitlist and post-transplant survival benefit in VA-ECMO bridged patients during the POST era. Similarly, we previously observed 12 significant waitlist benefits for POST era IABP-supported (status 2) patients bridged to heart transplantation without any difference in post-transplant survival. Additionally, our analysis identified a nearly 3-fold increase in the number of patients undergoing heart transplantation from mechanical ventilation.…”
Section: Limitationssupporting
confidence: 71%
“…An analysis of Status 1 patients bridged to heart transplantation with veno‐arterial extracorporeal membrane oxygenation (VA‐ECMO) identified reduced waitlist mortality, with shorter waitlist times, and improved post‐transplant survival 3 . Prior analyses demonstrated shorter waitlist times, reduced waitlist mortality and equivocal post‐transplant survival in patients bridged to heart transplant with an intra‐aortic balloon pump (IABP) 5,11,12 . One current limitation is that most analyses have examined outcomes for either all statuses or have focused on high‐priority (Status 1 and Status 2) patients alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3-8 Despite initial concerns, several recent reports have shown that this change in clinical practice had no detrimental effect on survival rates, nonfatal major cardiac events, freedom from cardiac allograft vasculopathy, or the incidence of rejection after heart-alone transplantation (HAT) at 1 y. 7-11…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Despite initial concerns, several recent reports have shown that this change in clinical practice had no detrimental effect on survival rates, nonfatal major cardiac events, freedom from cardiac allograft vasculopathy, or the incidence of rejection after heart-alone transplantation (HAT) at 1 y. [7][8][9][10][11] Renal dysfunction is relatively common in patients with end-stage HF owing to the cardiorenal syndrome, recurrent episodes of acute kidney injury, and high-dose diuretic requirements. 12,13 Given its association with poor clinical outcomes, many centers use an estimated glomerular filtration rate (eGFR) of 30 mL/min as a relative contraindication to HAT [14][15][16] and as the threshold to consider simultaneous heart-kidney (SHK) transplantation for appropriate candidates.…”
Section: Introductionmentioning
confidence: 99%